Application of omega 3,6 with Moringa oleifera suplemented vitamin E on rumen fluid characteristics, microbial protein synthesis, and methane gas production in goats on suboptimal lands - Angelia Utari; Rikardo Silaban; Novita Aswan; Toga Mahaji (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2024)
Changes in feeding patterns were needed to overcome the problem of methane gas emissions from ruminant livestock and the problem of low productivity at the smallholder livestock level. This solution involves direct action against the gas produced in the stomach of ruminants by providing feed containing active substances to reduce the microbes that produce gas in the stomach. One alternative feed that was often used as a promoter of improving rumen fluid characteristics was the use of omega 3.6 sources together with Moringa leaves enriched with vitamin E. This research aimed to investigate the effect of feeding on methane gas production in goats. The research method used a Randomized Block Design (RAK) with four treatments and five replications in vitro. From the research results, it could be concluded that the use of omega 3.6 together with Moringa leaves enriched with vitamin E was able to reduce methane gas production by 25.62% with a Volatile Fatty Acid (VFA) value of 144.53 mM, pH around 6.99, NH3 11.87 mg/100ml, microbial biomass 20.42 mg/ml, microbial protein 217.58mg/ml, bacterial colony 5.34x109 cells/ml and protozoa population 29x106 cells/ml. This conclusion shows that the use of omega 3.6 with Moringa oleifera supplemented with vitamin E has the potential to consistently improve rumen fluid characteristics and reduce methane gas emissions by using a combination of omega 3.6 sources and Moringa leaves in suboptimal land, as well as vitamin E supplementation.